Work Ethic and Cultural Identity of Kaili Doi Fishermen: A Thematic Analysis In Towale Village, Central Sulawesi - Akramullah, Ahmad (Aceh Anthropological Journal, 2025)
The condition of traditional fishermen in Towale Village is still concerning, but their enthusiasm and efforts never fade in carrying out their activities as traditional fishermen. The purpose of this study is to determine how the work ethic of traditional fishermen as a cultural identity of kaili fishermen in Towale Village, Central Sulawesi. This study uses a qualitative method with a descriptive type. This research was conducted in Towale Village, Central Sulawesi. Informants in this study numbered 6 people consisting of 1 key informant and 5 regular informants. The determination of informants used purposive sampling. The data collection techniques were carried out through observation, interviews, and documentation. After data collection, the researcher selected and grouped data in accordance with the research objectives, and focused on data that were considered important, so as to provide a clearer picture. Next, the author made more details and explanations of the data that had been found to more easily achieve the research objectives. The results of this study indicate that the work ethic of traditional fishing communities is related to the work motivation of each individual to achieve a certain goal or ideal so that the fishermen's work ethic is formed by the motivation and drive that radiates from their fundamental attitude towards work. Upholding honesty is a noble work ethic that is absolutely necessary and non-negotiable, if you want to become a superior professional with noble morals. The fishing community in Towale Village certainly also has its own motivation that makes them diligent and sincere in working and producing something valuable. Abstrak: Tujuan Nelayan tradisional di Desa Towale keadaannya masih memperihatinkan namun, semangat dan usaha mereka tidak pernah pudar dalam melakukan aktivitas sebagai nelayan tradisional. Tujuan penelitian ini untuk mengetahui tentang bagaimana etos kerja nelayan tradisional sebagai identitas kultural pada nelayan kaili doi di Desa Towale Sulawesi Tengah. Penelitian ini menggunakan metode kualitatif dengan tipe deskriptif. Penelitian ini dilakukan di Desa Towale Sulawesi Tengah. Informan dalam penelitian ini berjumlah 6 orang yang terdiri dari 1 informan kunci dan 5 informan biasa. Penentuan informan menggunakan porposive sampling. Adapun teknik pengumpulan data di lakukan dengan cara observasi, wawancara dan dokumentasi. Setelah pengumpulan data, peneliti memilih dan mengelompokkan data yang sesuai dengan tujuan penelitian, serta memfokuskan pada data-data yang dianggap penting, sehingga dapat memberikan gambaran yang lebih jelas. Selanjutnya, penulis membuat secara lebih rinci dan penjelasan terhadap data yang telah ditemukan agar lebih mudah mencapai tujuan penelitian.Hasil penelitian ini menunjukkan bahwa Etos kerja masyarakat nelayan tradisional berkaitan dengan motivasi kerja setiap individu untuk mencapai suatu tujuan atau cita-cita tertentu sehingga etos kerja para nelayan terbentuk oleh adanya motivasi dan dorongan yang terpancar dari sikap hidupnya yang mendasar terhadap kerja. Menjunjung tinggi kejujuran merupakan etos kerja mulia yang mutlak di perlukan dan tidak dapat ditawar lagi, kalau ingin menjadi profesional unggul berakhlak mulia. Masyarakat nelayan di Desa Towale tentunya juga memiliki motivasi sendiri-sendiri yang membuat mereka tekun dan ikhlas dalam bekerja dan menghasilkan sesuatu yang berharga.